2017
DOI: 10.1038/s41598-017-13608-5
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic Community Distribution along an Ecological Gradient of Salinity in Surface and Subsurface Saline Soils

Abstract: Salinity effects on microbial communities in saline soils is still unclear, and little is known about subsurface soil microbial communities especially in saline or hypersaline ecosystems. Here we presented the survey of the prokaryotic community in saline soils along a salinity gradient (17.3–148.3 dS/m) in surface (0–10 cm) and subsurface (15–30 cm) saline soils of Qarhan Salt Lake, China. Moreover, we compared them with three paired nonsaline normal soils. Using the high-throughput sequencing technology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 63 publications
10
24
2
Order By: Relevance
“…These soils were classified as sandy loam according to USDA textural classification system. Organic carbon content was in the range of the values reported for saline soils of La Sal del Rey (Edinburg, TX, USA) [ 18 ] and Sicily (Italy) [ 10 ], but lower than those found in saline soils of Qarhan Salt Lake (China) [ 5 ]. Nitrogen contents of the studied mineral soils are similar to those of the study of Hollister et al [ 18 ] and Pandit et al [ 19 ].…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…These soils were classified as sandy loam according to USDA textural classification system. Organic carbon content was in the range of the values reported for saline soils of La Sal del Rey (Edinburg, TX, USA) [ 18 ] and Sicily (Italy) [ 10 ], but lower than those found in saline soils of Qarhan Salt Lake (China) [ 5 ]. Nitrogen contents of the studied mineral soils are similar to those of the study of Hollister et al [ 18 ] and Pandit et al [ 19 ].…”
Section: Resultsmentioning
confidence: 80%
“…However, with that in mind, we attempted to situate our study in the context of the available literature about saline soils microbiota, using proposed conversions when necessary [ 65 ]. We found that the soils considered in our study were in the range of the saline soils studied by Xie et al from Qarhan Salt Lake (China) [ 5 ] and highest salinity soils addressed by Hollister et al [ 18 ], Canfora et al [ 10 ], Pandit et al [ 19 ] and Navarro-Noya et al [ 14 ] from La Sal del Rey (Edinburg, TX, USA), Sicily, the Great Rann of Kutch desert (Gujarat, India) and the former Lake Texcoco (Mexico), respectively.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Microbial communities are ubiquitous and can even thrive in extreme environments such as hypersaline lakes, marine habitats and saline–alkaline soils ( Jiang et al, 2007 ; Andrei et al, 2015 ; Yakimov et al, 2015 ; Xie et al, 2017 ). They are key components of these extreme ecosystems, and thus play central roles in their geochemical cycles and ecological stability ( Nunoura et al, 2013 ; Liang et al, 2014 ; Sorokin et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%